2012
DOI: 10.1093/nar/gks1043
|View full text |Cite
|
Sign up to set email alerts
|

Natural zinc ribbon HNH endonucleases and engineered zinc finger nicking endonuclease

Abstract: Many bacteriophage and prophage genomes encode an HNH endonuclease (HNHE) next to their cohesive end site and terminase genes. The HNH catalytic domain contains the conserved catalytic residues His-Asn-His and a zinc-binding site [CxxC]2. An additional zinc ribbon (ZR) domain with one to two zinc-binding sites ([CxxxxC], [CxxxxH], [CxxxC], [HxxxH], [CxxC] or [CxxH]) is frequently found at the N-terminus or C-terminus of the HNHE or a ZR domain protein (ZRP) located adjacent to the HNHE. We expressed and purifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 75 publications
1
52
0
Order By: Relevance
“…Also, lambda gpFI, an endonuclease, interacts with lambda terminase (16). Many phages encode an HNH protein (endonuclease) located adjacent to the phage DNA-packaging enzyme terminase, suggesting roles in phage DNA packaging and maturation (33). It is important and interesting that all of the phages, including mycobacteriophage Giles, harboring hnh genes are cos phages with linear DNA containing cohesive ends.…”
Section: Discussionmentioning
confidence: 99%
“…Also, lambda gpFI, an endonuclease, interacts with lambda terminase (16). Many phages encode an HNH protein (endonuclease) located adjacent to the phage DNA-packaging enzyme terminase, suggesting roles in phage DNA packaging and maturation (33). It is important and interesting that all of the phages, including mycobacteriophage Giles, harboring hnh genes are cos phages with linear DNA containing cohesive ends.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that many phages, infecting both Gram-positive and -negative bacteria, encode an HNH protein adjacent to the genes encoding the TerS, TerL, and portal proteins (20). Interestingly, all of the characterized phages carrying an hnh gene are cos phages.…”
Section: Geobacter Metallireducens Pseudomonas Alcaligenes Pacimentioning
confidence: 99%
“…The frequent juxtaposition of HNH and phage terminase genes (10,20) suggests a unique role for HNH proteins in the endonuclease and/or packaging activities of the terminases. To address this issue, we investigated the function of E. coli phage HK97 gp74, a 119-residue protein containing an HNH motif.…”
mentioning
confidence: 99%